Interactive effects of plant growth regulators and nitrogen on corn growth and nitrogen use efficiency. (18th September 2016) - Otie, Victoria; Ping, An; John, N. M.; Eneji, A. Egrinya
ABSTRACT: Our objective was to determine the combined effect of some plant growth regulators and nitrogen (N) on corn growth, yield and nitrogen use efficiency. A potted experiment was conducted with two levels of growth regulators [i.e. with or without treatment with Seed king (Kinetine), Root king (Indole-butyric acid) and More king (Chitosan)], two maize cultivars (Calabar White and Obatanpa-98 and three nitrogen rates (0, 90 and 180 kg/ha in the form of urea). The measured parameters were growth attributes, nitrogen uptake, dry matter yield, harvest-index, shoot to root ratio, yield attributes and agronomic and physiological nitrogen use efficiency. Calabar White had taller plants (154.53 cm) more leaves (12.00) and larger leaf area (466.98 cm 2 ) than obatanpa-98 at 6 weeks after sowing. The dry matter yield of both leaf and stem increased significantly (P ≤ 0.05) with increasing N rates but the growth regulators significantly (P ≤ 0.05) increased only the leaf dry matter. The interaction between growth regulators and nitrogen significantly affected the leaf dry matter but not the stem dry matter. There was a considerable (P ≤ 0.05) increase in harvest-index (HI) at the 90 kg/ha N rate with growth regulators and Obatanpa-98 had better HI (30.81%) than Calabar White (27.41%). Obatanpa 98 also had much (P ≤ 0.05) higher grain yield (87.42 g/plant) than Calabar White (65.40 g/plant) but for both cultivars, the grain yield increased progressively with increasing N rate. The uptake of N differed significantly (P ≤ 0.05) among the different partitions of maize (leaves, stems and grains) at various growth stages. Calabar White had the highest N uptake in the leaves and stem whether at silking or at harvest. Obatanpa-98 partitioned more N to the grains than Calabar White. Agronomic nitrogen use efficiency (ANUE) was highest (21.31 gg −1 ) at the 90 kg/ha N rate with Obatanpa-98 having a superior (20.26 gg −1 ) ANUE to Calabar White (15.94 gg −1 ). The physiological nitrogen use efficiency (PNUE) was also highest (8.14 g/kg) at the 90 kg/ha N rate with Obatanpa-98 being more efficient (8.08 gkg) than Calabar White (6.26 g/kg). Thus, both cultivars treated with 90 kgN/ha with or without growth regulators would best optimize nitrogen fertilizer use. However, the growth regulators increased the yield of Calabar White significantly only when no N was applied. In contrast, they increased the yield of the hybrid Obatanpa-98 at all N rates especially at the 180 kgN/ha rate. Thus, under the low input cropping common with Calabar White, treatment with the growth regulators would boost yield. A combined treatment of 180 kg N/ha with the growth regulators would ensure the best yield of Obatanpa-98.